Zoonotic approach to Shiga toxin-producing Escherichia coli: integrated analysis of virulence and antimicrobial resistance in ruminants and humans. (2019) - Oporto, B.; Ocejo, M.; Alkorta, M.; Marimón, J. M.; Montes, M.; Hurtado, A.
Abstract: In 2014–2016, we conducted a cross-sectional survey in 115 sheep, 104 beef and 82 dairy cattle herds to estimate Shiga toxin-producing Escherichia coli (STEC) prevalence, and collected data on human clinical cases of infection. Isolates were characterised ( stx 1, stx 2, eae, ehx A) and serogroups O157 and O111 identified by PCR, and their antimicrobial resistance (AMR) profiles were determined by broth microdilution. STEC were more frequently isolated from beef cattle herds (63.5%) and sheep flocks (56.5%) than from dairy cattle herds (30.5%) ( P < 0.001). A similar but non-significant trend was observed for O157:H7 STEC. In humans, mean annual incidence rate was 1.7 cases/100 000 inhabitants for O157 STEC and 4.7 for non-O157 STEC, but cases concentrated among younger patients. Distribution of virulence genes in STEC strains from ruminants differed from those from human clinical cases. Thus, stx 2 was significantly associated with animal STEC isolates (O157 and non-O157), ehx A to ruminant O157 STEC ( P = 0.004) and eae to human non-O157 STEC isolates ( P < 0.001). Resistance was detected in 21.9% of human and 5.2% of animal O157 STEC isolates, whereas all non-O157 isolates were fully susceptible. In conclusion, STEC were widespread in ruminants, but only some carried virulence genes associated with severe disease in humans; AMR in ruminants was low but profiles were similar to those found in human isolates.